2009
DOI: 10.3844/ajassp.2009.1321.1326
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effects of Non-Tariff Barriers on the Export of the Main Agricultural Products of Iran

Abstract: Problem statement: As trade agreements decrease tariffs throughout the world, other barriers to trade emerge. These Non-Tariff Barriers (NTBs) can be just as troublesome as tariffs for exporting countries. NTBs include any of a number of hindrances that restrict the ability of companies to export. NTBs may now have a greater impact on trade than tariffs. Approach: In contrast with previous research, we used a gravity model to estimate the trade effect of non-tariff barriers imposed by importer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…It was expected that improved relative prices would diminished trade deficit in the long-run, but the occurrence of debt crisis in 1994 and high shrinkage of imports due to quantitative limits, revealed that the policy makers, lacked power to improve the trade balance flow [1,2,8] . In the period after Islamic revolution, the agricultural trade balance was always negative.…”
Section: Introductionmentioning
confidence: 99%
“…It was expected that improved relative prices would diminished trade deficit in the long-run, but the occurrence of debt crisis in 1994 and high shrinkage of imports due to quantitative limits, revealed that the policy makers, lacked power to improve the trade balance flow [1,2,8] . In the period after Islamic revolution, the agricultural trade balance was always negative.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of aflatoxin standards on the pistachio trade has been examined in a large number of studies (Alaeibakhsh & Ardakani, 2012; Ardakani et al, 2009; Bui‐Klimke et al, 2014; Wu, 2008; Zheng et al, 2012). Wu (2008) analyses the impact of the strict EU aflatoxin standards on US almond and pistachio exports from 1998 to 2004.…”
Section: Influence Of Food Safety On Trade: Empirical Evidencementioning
confidence: 99%
“…Following WTO rules, countries adopt regulations under the sanitary and phytosanitary (SPS) measures and technical barriers to trade (TBT) agreements to protect human, animal, and plant health as well as the environment, wildlife, and human safety. Although SPS measures are not implemented to restrict trade, in the practice they can impede the entry of imports into a country (Ardakani et al, 2009; Chen et al, 2008). However, the effect of NTMs on trade is not always clear, and generalizations should be avoided (Beghin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental concept of the gravity model is that the attraction between two objects is proportional to their mass and inversely proportional to their respective distance. Consequently, the general formulation of spatial interactions can be adapted to reflect this basic assumption to form the elementary formulation of the gravity model using impedance variables (e.g., distance, travel time, generalized cost) to describe the way in which freight demand decreases (Ogden, 1978;Toosi et al, 2009;Ardakani et al, 2009). The gravity model calibration process attempts to explore the impedance variable function as closely as possible using the observed trip length distribution (Ortuzar and Willumsen, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%